JQuery Mobile - Reid, Jon (O'Reilly, 2011)
The future belongs to mobile web apps that function on a broad range of smart-phones and tablets. Get started with jQuery Mobile, the touch-optimized framework for creating apps that look and behave consistently across many devices. This book assumes that you are already familiar with the jQuery JavaScript library, HTML markup, Cascading Style Sheets, and mobile web browsers. The book provides HTML5, CSS3, and JavaScript code examples, screen shots, and step-by-step guidance to help you build a complete working app.